2013
DOI: 10.1038/modpathol.2012.130
|View full text |Cite
|
Sign up to set email alerts
|

Marked heterogeneity of ERG expression in large primary prostate cancers

Abstract: Approximately 50% of prostate cancers are characterized by TMPRSS2 (transmembrane protease serine 2)-ERG (avian v-ets erythroblastosis virus E26 oncogene homolog) gene fusions resulting in an androgen-regulated overexpression of the transcription factor ERG. Some studies have suggested prognostic or predictive relevance of ERG status in prostate cancer. Such concepts could be impaired by extensive ERG heterogeneity in analyzed tumors. The aim of this study was to analyze the extent of heterogeneity for TMPRSS2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
52
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 59 publications
(61 citation statements)
references
References 30 publications
8
52
0
1
Order By: Relevance
“…Genetic prediction tools may also add significant costs to the PCa diagnostic and therapeutic algorithms, but these costs might be justified if indeed they lead to a reduction in unnecessary treatments for localized disease or a more appropriate selection of therapy for advanced disease. An important aspect of biomarker and genetics research is the heterogeneity of PCa both within a single tumor locus (intrafocal heterogeneity) and between different tumor deposits (interfocal heterogeneity) [96][97][98]. In addition to intra/interfocal heterogeneity, a field effect of genetic changes should also be considered because cancer-related genetic changes are also detected in benign areas of the same prostate [99].…”
Section: Discussionmentioning
confidence: 99%
“…Genetic prediction tools may also add significant costs to the PCa diagnostic and therapeutic algorithms, but these costs might be justified if indeed they lead to a reduction in unnecessary treatments for localized disease or a more appropriate selection of therapy for advanced disease. An important aspect of biomarker and genetics research is the heterogeneity of PCa both within a single tumor locus (intrafocal heterogeneity) and between different tumor deposits (interfocal heterogeneity) [96][97][98]. In addition to intra/interfocal heterogeneity, a field effect of genetic changes should also be considered because cancer-related genetic changes are also detected in benign areas of the same prostate [99].…”
Section: Discussionmentioning
confidence: 99%
“…To facilitate such whole tumor analyses, we have previously developed a prostate cancer heterogeneity tissue microarray (tissue microarray) platform. 2 This tissue microarray platform contains samples from 10 distant tumor areas each of 189 large prostate cancers, thus enabling a high-throughput mapping of molecular features across the entire tumors. Our initial analysis of this tissue microarray revealed that the prostate cancer-specific TMPRSS2:ERG fusions is heterogeneous in 470% of ERG-positive prostate cancers.…”
mentioning
confidence: 99%
“…Our initial analysis of this tissue microarray revealed that the prostate cancer-specific TMPRSS2:ERG fusions is heterogeneous in 470% of ERG-positive prostate cancers. 2 Inactivation of the phosphatase and tensin homolog (PTEN) gene by genomic deletion or rearrangement, including intragenic breakage and translocation, is another key molecular event in prostate cancer. PTEN deletion or rearrangement has been reported in 20-30% of prostate carcinomas, and is linked to particularly aggressive cancers.…”
mentioning
confidence: 99%
“…Современные данные [61][62][63][64] показывают, что в от-дельных опухолевых очагах почти всегда имеется значи-мая внутриочаговая гетерогенность в отношении образо-вания слияний TMРRSS2: ERG и его структуры, в отношении потери PTEN, геномных аберраций и эпигенетических изменений всего генома. В большин-стве случаев эти генетически различные опухоли кажутся идентичными внешне и по степени дифферен цировки будут классифицированы одинаково.…”
Section: обзорunclassified